Role of accounting and audit in the recent financial crisis - (:unkn) unknown (IGI Global, 2013)
This study aims to assess the role of accounting and auditing in the recent financial crisis. After each crisis, there have been serious discussions concerning the reasons behind those crises. However, no consensus has yet been achieved until now. In this context, the analysis of the relationships among financial crisis, accounting, and auditing is of utmost importance in better evaluating the structural reasons behind the crisis. There are several points that this chapter aims to analyze to indicate the contributions of accounting and auditing to the recent global financial crisis. These points are: impacts of disregarding the main principles of accounting, the wide use of fair value accounting over cost-based accounting, incorrect and misleading financial and audit reports, applications of creative accounting, and lack of transparency and weaknesses of the auditing process. The debates generally concentrate on the use of fair value (mark-tomarket) accounting in the financial reports as opposed to the historical cost method. It should be emphasized that accounting is very important as a key mechanism of market economies, because of its crucial role in the functioning of the markets in accordance with the public interest. The chapter concludes with several suggestions by taking the fact into consideration that accounting and auditing systems should be revised for the better protection of interests of the third parties such as investors, potential investors, and the state. © 2014, IGI Global.